2016
DOI: 10.1093/pasj/psw070
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the characteristic X-ray spectral variations of IRAS 13224−3809

Abstract: The Narrow-line Seyfert 1 galaxy (NLS1) IRAS 13224−3809 is known to exhibit significant Xray spectral variation, a sharp spectral drop at ∼ 7 keV, strong soft excess emission, and a hint of iron L-edge feature, which is very similar to the NLS1 1H 0707−495. We have proposed the "Variable Double Partial Covering (VDPC) model" to explain the energy spectra and spectral variability of 1H 0707−495 (Mizumoto, Ebisawa and Sameshima 2014, PASJ, 66, 122). In this model, the observed flux/spectral variations below 10 k… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…We have shown that 'double partial covering' with the same partial covering fractions can explain the observed spectral/flux variability of NGC 4051 in the 0.4-10 keV. Indeed, equation 13is equivalent to the 'variable double partial covering (VDPC) model', which was originally proposed for MCG-6-30-15 by Miyakawa, Ebisawa & Inoue (2012), refined by Mizumoto et al (2014), and confirmed for various NLS1s by Iso et al (2016) and Yamasaki et al (2016). In the VDPC model, the commonality of the two partial covering fractions is explained by double-layer absorbers, and the spectral variations of NLS1s are explained by the partial covering fraction of the double-layer absorbers, as well as independent variation of the continuum normalization.…”
Section: Variable Double Partial Covering Modelmentioning
confidence: 70%
See 1 more Smart Citation
“…We have shown that 'double partial covering' with the same partial covering fractions can explain the observed spectral/flux variability of NGC 4051 in the 0.4-10 keV. Indeed, equation 13is equivalent to the 'variable double partial covering (VDPC) model', which was originally proposed for MCG-6-30-15 by Miyakawa, Ebisawa & Inoue (2012), refined by Mizumoto et al (2014), and confirmed for various NLS1s by Iso et al (2016) and Yamasaki et al (2016). In the VDPC model, the commonality of the two partial covering fractions is explained by double-layer absorbers, and the spectral variations of NLS1s are explained by the partial covering fraction of the double-layer absorbers, as well as independent variation of the continuum normalization.…”
Section: Variable Double Partial Covering Modelmentioning
confidence: 70%
“…Equations (5) and (7) are mathematically equivalent; both equations monotonically increase with σ (E), which means that rms peaks appear at the energy band where the absorption features are deeper than the adjacent bands (see fig. 10 of Yamasaki et al 2016). We calculated simulated rms spectra in order to illustrate effects of the warm absorber variations in the rms spectra.…”
Section: Absorption/emission Featuresmentioning
confidence: 99%
“…Such variable partial covering models can fit the observed spectral variability (e.g. Miyakawa et al 2012;Mizumoto et al 2014;Iso et al 2016;Yamasaki et al 2016). The occultation timescale is t occ ∼ 2000(M BH /2 × 10 6 M ⊙ )(R/500 R g ) 1/2 (D/10 R g ) s (Mizumoto & Ebisawa 2017), where R and D are the location and size of the cold clumps, respectively.…”
Section: Complex Absorption In the Clumpy Windmentioning
confidence: 98%
“…This restricts the results that can be obtained, and makes comparison between different spectra difficult. The typical analysis of such a spectrum is a qualitative examination by eye, and a more sophisticated analysis will include comparison with a simulated spectrum based on the model fit to the count spectrum (e.g., Vaughan & Fabian 2004;Matzeu et al 2016;Yamasaki et al 2016;Mallick et al 2017;Alston et al 2020).…”
Section: Introductionmentioning
confidence: 99%